Overrepresentation of the COL3A1 AA genotype in Polish skiers with anterior cruciate ligament injury - M Stępień-Słodkowska; K Ficek; A Maciejewska-Karłowska; M Sawczuk; P Ziętek; P Król; P Zmijewski; A Pokrywka; P Cięszczyk (Termedia Publishing House, 2015)
Although various intrinsic and extrinsic risk factors for anterior cruciate ligament (ACL) rupture have been identified, the exact aetiology of the injury is not yet fully understood. Type III collagen is an important factor in the repair of connective tissue, and certain gene polymorphisms may impair the tensile strength. The aim of this study was to examine the association of the COL3A1 rs1800255 polymorphism with ACL rupture in Polish male recreational skiers. A total of 321 male Polish recreational skiers were recruited for this study; 138 had surgically diagnosed primary ACL ruptures (ACL-injured group) and 183 were apparently healthy male skiers (control group - CON) who had no self-reported history of ligament or tendon injury. Both groups had a comparable level of exposure to ACL injury. Genomic DNA was extracted from the oral epithelial cells. All samples were genotyped on a real-time polymerase chain reaction instrument. The genotype distribution in the ACL-injured group was significantly different than in CON (respectively: AA=10.1 vs 2.2%, AG=22.5 vs 36.1, GG=67.4 vs 61.8%; p=0.0087). The AA vs AG+GG genotype of COL3A1 (odds ratio (OR) = 5.05; 95% confidence interval (CI), 1.62-15.71, p = 0.003) was significantly overrepresented in the ACL-injured group compared with CON. The frequency of the A allele was higher in the ACL-injured group (21.4%) compared with CON (20.2%), but the difference was not statistically significant (p=0.72). This study revealed an association between the COL3A1 rs1800255 polymorphism and ACL ruptures in Polish skiers.